Structural and magnetodielectric properties of BiFeO3-GdMnO3 multiferroics. (29th January 2021) - Masso, R; Tripathy, S N; Aponte, F A; Pradhan, D K; Martinez, R; Palai, R
Abstract: We report on structural, microstructural, spectroscopic, dielectric, electrical, ferroelectric, ferromagnetic, and magnetodielectric coupling studies of BiFeO3 –GdMnO3 [(BFO)1– x –(GMO) x ], where x is the concentration of GdMnO3 ( x = 0.0, 0.025, 0.05, 0.075, 0.1, 0.15, and 0.2), nanocrystalline ceramic solid solutions by auto-combustion method. The analysis of structural property by Rietveld refinement shows the existence of morphotropic phase boundary (MPB) at x = 0.10, which is in agreement with the Raman spectroscopy and high resolution transmission electron microscopy (HRTEM) studies. The average crystallite size obtained from the transmission electron microscopy (TEM) and x-ray line profile analysis was found to be 20–30 nm. The scanning electron micrographs show the uniform distribution of grains throughout the surface of the sample. The dielectric dispersion behavior fits very well with the Maxwell-Wagner model. The frequency dependent phase angle ( θ ) study shows the resistive nature of solid solutions at low frequency, whereas it shows capacitive behavior at higher frequencies. The temperature variation of dielectric permittivity shows dielectric anomaly at the magnetic phase transition temperature and shifting of the phase transition towards the lower temperature with increasing GMO concentration. The Nyquist plot showed the conduction mechanism is mostly dominated by grains and grain boundary resistances. The ac conductivity of all the samples follows the modified Jonscher model. The impedance and modulus spectroscopy show a non-Debye type relaxation mechanism which can be modeled using a constant phase element (CPE) in the equivalent circuit. The solid-solutions of BFO-GMO show enhanced ferromagnetic-like behavior at room temperature. The ferroelectric polarization measurement shows lossy ferroelectric behavior. The frequency dependent magnetocapacitance and magnetoimpedance clearly show the existence of intrinsic magnetodielectric coupling. The (BFO)1– x –(GMO) x solid solutions with x = 0.025–0.075 show significantly higher magnetocapacitance and magnetoimpedance compared to the pure BFO.